THE APPLICATION OF RESPONSIBILITY EDUCATION ON SUSTAINABILITY ISSUES - Tsai, Shieunt-Han; Yang, I-H (Graduate Program of Universitas Tarumanagara, 2023)
People start to rethink if to sacrifice the ecology for the prosperity of the various industries for a better life. Responding to the United Nations 2030 Sustainable Development Goal SDGs 4